2014
DOI: 10.1021/jp509388j
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Atomic Structure of Cycled Lithium-Rich Layered Oxide Li1.20Mn0.54Co0.13Ni0.13O2 Using HAADF STEM and Electron Nanodiffraction

Abstract: Insight in the Atomic Structure of Cycled Lithium-rich Layered Oxide Li1.20Mn0.54Co0.13Ni0.13O2 using HAADF STEM and Electron Nano Diffraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 36 publications
10
118
0
Order By: Relevance
“…25,[27][28][29] However, using a material with a very high lithium content, like the 0.50 Li 2 MnO 3 material in this study, a partial bulk transformation can be observed, amounting to ≈20 mol% of the material being converted into a spinel-like phase (calculated from the oxygen evolution, shown in Model II from Table IV). While the TEM data are statistically not sufficient to provide exact quantitative surface layer thickness values for averaged over the entire material, they fit well to the quantification from the OEMS results.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…25,[27][28][29] However, using a material with a very high lithium content, like the 0.50 Li 2 MnO 3 material in this study, a partial bulk transformation can be observed, amounting to ≈20 mol% of the material being converted into a spinel-like phase (calculated from the oxygen evolution, shown in Model II from Table IV). While the TEM data are statistically not sufficient to provide exact quantitative surface layer thickness values for averaged over the entire material, they fit well to the quantification from the OEMS results.…”
Section: Discussionmentioning
confidence: 72%
“…25 Both observations suggested that the observed oxygen release cannot be ascribed to a loss of oxygen from the bulk of the material, but that the oxygen is only being released from the near-surface Thus, more recent studies propose that bulk and surface of these overlithiated materials show distinctly different properties, rationalized by a bulk-shell model. 25,[27][28][29] It has been suggested that oxygen release takes places in near-surface region, leading to a chemical layered-to-spinel transformation and a concomitant impedance buildup by the formed resistive surface layer. This phenomenon has also been shown to be one of the main fading mechanisms for traditional NCM materials.…”
mentioning
confidence: 99%
“…Delmas et al, successfully investigate the structural rearrangement of 1 st cycled Li-excess 3dTM material along [100] mono zone axis 36 . In order to analyze the structural characteristic of Li-excess material correctly, Atomic arrangement along [100] mono direction where we can observe Li 2 MnO 3 phase is additionally needed to increase the structural analysis accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…From the amount of evolved gases, we estimated the thickness of such a spinel-like surface layer on the HE-NCM particles to be on the order of ≈2-3 nm, in excellent agreement with previously observed (S)TEM data. [28][29][30] …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the estimated thickness of ≈2-3 nm for the spinel-like phase is in excellent agreement with recent (S)TEM results, which propose also a 2-3 nm thick surface layer formed during the first cycle. [28][29][30] As already mentioned in the discussion of Figure 2, it is not possible to determine whether the transformation of the near-surface region stops at the spinel structure (as described in Eq. 2) and to what extent it may proceed all the way to the rock-salt structure (as described in Eq.…”
Section: Ammentioning
confidence: 99%